BADANIA KLINICZNE I DOŚWIADCZALNE W CHOROBACH SERCA, PŁUC I NACZYŃDependence of primary graft dysfunction on ischaemia time in an experimental model of lung transplantation - Kubisa, Bartosz; Pieróg, Jarosław; Wójcik, Janusz; Alchimowicz, Jacek; Kozak, Anna; Bielewicz, Michał; Witkowska, Dominika; Wojtyś, Małgorzata; Pankowski, Juliusz; Skrzydlewska, Elżbieta; Droździk, Marek; Grodzki, Tomasz (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2008)
Aim: To evaluate the effect of primary graft dysfunction (PGD) in relation to the total ischaemia time with or without application of colchicine. Material and Methods: Isogeneic, orthotropic single left lung transplantations were conducted among male Wistar rats after total ischaemia time of 12 or 18 hours at a temperature of 4°C. The recipients received either no medication (A group) or colchicine 600 µg/kg ip one hour before transplantation and 12 hours after the first dose (group B). After 24 hours the right principal bronchus and right pulmonary artery were occluded to assess graft gas exchange function (PaO2). The graft was then excised to assess wet/dry ratio (W/D) as a measure of pulmonary oedema, and myeloperoxidase activity (MPO) as a measure of neutrophil migration and histology. Student’s T-test for paired data was used for statistical analysis. The data are presented as mean ± standard deviation. Results: PaO2 values were poor in all groups and the differences were statistically not significant (p>0.05). The group A W/D ratio after 18 hours of total ischaemia time was 1.86±0.32 in comparison to 5.70±1.53 after 12 hours, p=0.007. The group B W/D ratio after 18 hours of total ischaemia time was 3.93±0.66 vs. 5.40±1.49 after 12 hours, p=0.049. The group A MPO activity was 5.87±1.76 after 18 hours vs. 8.96±1.86 µM/mg after 12 hours p=0.53. The group B MPO activity was 8.10±3.34 after 18 hours vs. 11.26±4.03 µM/mg after 12 hours, p=0.22. Histologically, the group B grafts showed lesser damage than in group A. Conclusion: The 18 hours total ischaemia time causes lesser PGD expressed by smaller lung oedema in comparison to 12 hours ischaemia time, independently of colchicine application. Colchicine does not improve the PGD course.